2018
DOI: 10.5114/hpr.2018.73052
|View full text |Cite
|
Sign up to set email alerts
|

An exploratory examination of mindfulness, self-compassion, and mindful eating in relation to motivations to eat palatable foods and BMI

Abstract: health psychology report · 8 original article background Preliminary findings suggest that mindfulness and selfcompassion training are associated with enhanced weight regulation. However, the associations between these traits and body mass index (BMI) are mixed. participants and procedureIn a cross-sectional investigation, university students (n = 183) were asked to fill in questionnaires on mindfulness, self-compassion, mindful eating, and motivations to eat palatable foods. resultsThe results suggest that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
20
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 31 publications
3
20
0
2
Order By: Relevance
“…Children at an early age have a tendency to avoid novel foods [ 1 ] and they have an innate predisposition to prefer sweet and salty tastes [ 51 ], and energy-dense foods [ 52 ]. Cross-cultural research indicates that children, unsurprisingly, prefer fries, pizza and ice-cream over meals with better nutritional value [ 13 , 35 , 53 ] and that these preferences are fairly stable over time [ 13 ] unless modified by parents [ 54 ]. If not exposed to a variety of foods and encouraged to taste unfamiliar flavours, children’s preferences will remain limited and they will continue to favour food of low nutritional value like snacks and sugared drinks [ 55 , 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…Children at an early age have a tendency to avoid novel foods [ 1 ] and they have an innate predisposition to prefer sweet and salty tastes [ 51 ], and energy-dense foods [ 52 ]. Cross-cultural research indicates that children, unsurprisingly, prefer fries, pizza and ice-cream over meals with better nutritional value [ 13 , 35 , 53 ] and that these preferences are fairly stable over time [ 13 ] unless modified by parents [ 54 ]. If not exposed to a variety of foods and encouraged to taste unfamiliar flavours, children’s preferences will remain limited and they will continue to favour food of low nutritional value like snacks and sugared drinks [ 55 , 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…Mindful eating assists in the gradual change of external eating and environmentally driven responses to food to internal decision-making and eating, promoting healthier eating behaviours (Mantzios andWilson 2014, 2015a;Mantzios and Giannou 2014), such as a decrease in external and emotional eating (Warren et al 2017;O'Reilly et al 2014), an increased intake of fruit and vegetables (Dutt et al 2018;Gilbert & Waltz, 2010), as well as a reduction in the consumption of high-sugar and energy-dense foods (Mason et al 2016). Research has found a negative association between mindful eating and fat and sugar consumption (Mantzios et al 2018a, b), grazing (Mantzios et al 2018a, b), motivations to eat palatable foods (Mantzios and Egan 2018), as well as weight gain (Mantzios, Wilson, Linnell & Morris, 2014). Overall, mindfulness specific to eating rather than mindfulness targeting more generically the self-regulation of attention has been found to be more effective in improving eating behaviours (Mantzios and Wilson 2015b;O'Reilly et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, Mantzios and Egan (2018) suggested that mindfulness, mindful eating and self-compassion enable and assist weight regulation through negative associations to motives to eat palatable foods, and implications for potential interventions to regulate food consumption. The practice of mindfulness is defined as an awareness that emerges through purposefully paying attention in the present moment, non-judgementally (Kabat-Zinn, 1990), with research acknowledging that being mindfully aware of food is helpful in regulating cravings and eating (e.g.…”
Section: Introductionmentioning
confidence: 99%